Pengaruh Perhatian Orangtua Terhadap Minat Belajar PAK Siswa Kelas XI SMA Swasta HKBP Doloksanggul Tahun Pembelajaran 2024/2025. - Santi Verawati Purba; Junjungan Simorangkir; Robinhot Sihombing; Raikapoor Raikapoor; Tahadodo Waruwu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The study aims to determine the effect of parental attention on the interest in learning PAK of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year. The research hypothesis is that there is a positive and significant influence between parental attention on the interest in learning PAK of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year. The quantitative research method is descriptive and inferential. The population of all class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year who are Protestant Christians is 159 people. The random sampling is 25% of the population, which is 40 people. The research instrument is a closed questionnaire. The results of the data analysis obtained: a) The value of r count = 0.647> r table = 0.312 and t count = 5.231> t table = 2.02439 indicates a positive and significant relationship between parental attention to the interest in learning PAK of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year. b) Regression equation. c) Determination test shows that the magnitude of the influence is 41.86%. d) Hypothesis test obtained F count = 27.411> F table = 3.23 then H0 is rejected and Ha is accepted. The study concludes that there is a positive and significant influence between parental attention to the interest in learning PAK of class XI students of HKBP Doloksanggul Private High School in the 2024/2025 Academic Year.